2021
DOI: 10.1016/j.redox.2021.102021
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the contribution of mitochondrial glutathione to ferroptosis in cardiomyocytes

Abstract: Ferroptosis is a programmed iron-dependent cell death associated with peroxidation of lipids particularly, phospholipids. Several studies suggested a possible contribution of mitochondria to ferroptosis although the mechanisms underlying mitochondria-mediated ferroptotic pathways remain elusive. Reduced glutathione (GSH) is a central player in ferroptosis that is required for glutathione peroxidase 4 to eliminate oxidized phospholipids. Mitochondria do not produce GSH, and although the transport of GSH to mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 47 publications
5
77
0
Order By: Relevance
“…Recent studies have shown that using gas cluster ion beam secondary ion mass spectrometry imaging can map PEox at ferroptotic H9c2 cardiomyoblasts [ 48 ]. In addition, LC-MS/MS analysis revealed a dramatic increase in PEox species in mitochondria in response to RSL3 and cardiac I/R [ 9 ]. A previous study showed that XN markedly decreases the level of lipid peroxidation and ROS production in rat liver [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that using gas cluster ion beam secondary ion mass spectrometry imaging can map PEox at ferroptotic H9c2 cardiomyoblasts [ 48 ]. In addition, LC-MS/MS analysis revealed a dramatic increase in PEox species in mitochondria in response to RSL3 and cardiac I/R [ 9 ]. A previous study showed that XN markedly decreases the level of lipid peroxidation and ROS production in rat liver [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…GPX4 not only catalyzes the peroxidation of hydrogen peroxide (H 2 O 2 ) but also detoxifies the lipid peroxides by reducing glutathione [ 8 ]. Jang et al reported that ferroptotic stimuli reduce mitochondrial bioenergetics, glutathione depletion, and GPX4 inactivation, leading to ferroptosis in cardiomyocytes [ 9 ]. Park et al indicated that downregulation of GPX4 during myocardial infarction contributes to ferroptotic cell death in cardiomyocytes upon metabolic stress [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…H9c2 cardioblasts were cultured according to the manufacturer’s recommendations (ATCC, Manassas, VA, USA) with minor modifications [ 12 ]. Briefly, the cells were incubated in DMEM based modified media containing 4 mM L-glutamine, 4.5 g/L glucose, 1 mM sodium pyruvate, and 1.5 g/L sodium bicarbonate, pH 7.4, and supplemented with 10% fetal bovine serum and 1% antibiotic solution (HyClone, Logan, UT, USA) in a CO 2 incubator containing 95% air and 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies suggested a direct link between ferroptosis and coronary heart diseases, particularly myocardial infarction and ischemia-reperfusion, in animal models and patients [ 8 , 9 , 10 , 11 , 12 ]. However, the mechanisms of ferroptosis signaling in the heart remain unknown, which represents a challenge for the development of new therapeutic strategies for coronary heart diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation